Poopsie gets lost - Harrison, Hannah E. (New York : Dial Books for Young Readers, 2022)
Pampered, nap-loving kitty Poopsie makes her way through a jungle after a pushy narrator pressures her toward adventure.
School Library Journal starred, May 2022
Booklist, March 2022
Kirkus Review, March 2022
2.1
K-3
Keywords: Cats -- Juvenile fiction; Jungles -- Juvenile fiction; Cats -- Fiction; Jungles -- Fiction; Action and adventure fiction; Animal fiction